2021
DOI: 10.1007/s40948-021-00230-z
|View full text |Cite
|
Sign up to set email alerts
|

Α comprehensive geotechnical characterisation of overburden material from lignite mine excavations

Abstract: For the sustainability of lignite and coal mining, engineers need the soils' appropriate geotechnical characterisation of the excavations. This characterisation relates to the slope stability, the overall area stability, and the sustainable exploitation of mining areas during operational and post-closure eras. This work presents a novel perspective on the soil characterisation of lignite mine excavations. Rather than focusing on one particular mine, a comprehensive geotechnical characterisation provides insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The decrease of  concomitant with the increase of C is a known phenomenon, verified by analysing the correlation between these 2 parameters (Theocharis et al 2021). The calculation of the correlation coefficient r shows, unsurprisingly, that the anti-correlation values correspond to the values that can be found in the literature (Theocharis et al 2021). The value of r varies between -0.11 and -0.83 with a mean value of -0.37 (Fig.…”
Section: Depth (M)supporting
confidence: 73%
“…The decrease of  concomitant with the increase of C is a known phenomenon, verified by analysing the correlation between these 2 parameters (Theocharis et al 2021). The calculation of the correlation coefficient r shows, unsurprisingly, that the anti-correlation values correspond to the values that can be found in the literature (Theocharis et al 2021). The value of r varies between -0.11 and -0.83 with a mean value of -0.37 (Fig.…”
Section: Depth (M)supporting
confidence: 73%
“…In this work, Greek lignite mines are employed for the soil properties that represent fine-grained materials. Theocharis et al [31] recently discussed an overview of the geotechnical characterization of the soil materials found in Greek lignite mines. Nevertheless, these properties are not specific to a site but characterize this type of surface mine slope.…”
Section: The Methodology and The Case Example Of Greek Lignite Minesmentioning
confidence: 99%
“…Finally, the soil's permeability, the main soil property related to infiltration, was parametrically investigated. The chosen saturated permeability lies in the range of the dominant overburden material of Greek open-pit lignite mines [31].…”
Section: Effect Of Rainfall On Slope Stabilitymentioning
confidence: 99%
“…The comparison was conducted for three weak zone inclinations towards the excavation, 0°, 3° and 6° (unfavourable inclination). For the numerical model, the soil's friction angle and cohesion were φ=28° and c=185kPa (Theocharis et al 2021), while the weak zone's thickness was d z =5m. Note that Mikroutsikos et al (2021) showed that the weak zone's thickness is insignificant for the overall stability.…”
Section: Numerical Model: Basic Assumptionsmentioning
confidence: 99%
“…The friction angle and cohesion of the homogeneous soil layer may vary in a wide range. A recent study shows that the average characteristic peak friction angle and cohesion for Greek lignite mines are 25° and 111kPa, respectively (Theocharis et al 2021). However, for individual mines, these values can be as low as 22° and 20kPa.…”
Section: Introductionmentioning
confidence: 99%